The Theoretical Foundations of Quantum Mechanics - Baaquie, Belal E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The Theoretical Foundations of Quantum Mechanics addresses fundamental issues that are not discussed in most books on quantum mechanics. This book focuses on analyzing the underlying principles of quantum mechanics and explaining the conceptual and theoretical underpinning of quantum mechanics. In particular, the concepts of quantum indeterminacy, quantum measurement and quantum superposition are analyzed to clarify the concepts that are implicit in the formulation of quantum mechanics. The Schrodinger equation is never solved in the book. Rather, the discussion on the fundamentals of quantum mechanics is treated in a rigorous manner based on the mathematics of quantum mechanics. The new concept of the interplay of empirical and trans-empirical constructs in quantum mechanics is introduced to clarify the foundations of quantum mechanics and to explain the counter-intuitive construction of nature in quantum mechanics. The Theoretical Foundations of Quantum Mechanics is aimed at the advanced undergraduate and assumes introductory knowledge of quantum mechanics. Its objective is to provide a solid foundation for the reader to reach a deeper understanding of the principles of quantum mechanics.
Preface -- Acknowledgments -- 1 Synopsis -- 2 The Quantum Entity and Quantum Mechanics -- 3 Quantum Mechanics: Empirical and Trans-empirical -- 4 Degree of Freedom F; State space V -- 5 Operators -- 6 Density matrix; Entangled states -- 7 Quantum indeterminacy -- 8 Quantum Superposition -- 9 Quantum Theory of Measurement -- 10 The Stern-Gerlach experiment -- 11 The Feynman Path Integral -- 12 Conclusions -- Glossary of Terms -- List of Symbols -- References -- Index.
Keywords: Physics; Quantum theory; Physics; Quantum Physics; Mathematical Physics; Quantum Optics; Mathematical Applications in the Physical Sciences; History and Philosophical Foundations of Physics